Análisis del proceso emocional de los padres con niños diagnosticados con trastornos de espectro Autista (TEA) del Centro Integral de Niños "Kraaker" - Ronquillo Luna, Adonis Isidoro (2025)
This research will address the relevance of emotional management in parents of children diagnosed with Autism Spectrum Disorder (ASD). Analyzing how adequate emotional management by parents can positively affect the emotional well-being and development of children with ASD. Seeking that the beneficiaries can understand the study once described and can acquire emotional regulation skills to provide a supportive environment. The total population to be studied is 116 parents, selecting a sample of 90 through simple probabilistic random sampling. A descriptive mixed approach and a non-experimental cross-sectional design will be used, together with the application of psychometric tests such as the Beck Anxiety Inventory (BAI) created by Aron T. Beck and several collaborators in 1988 and the Perceived Stress Scale (PSS-14) created by Sheldon Cohen and his collaborators in 1983.